Health Science Students as PPE Coaches in the Emergency Department – a Pandemic Pilot Project. Issue 2 (June 2021) - Wong, J.; Gallagher, M.; Friedt, J.; Trinder, K.; McKague, M.; Stevenson, K.; Cattell, V.
Summary: PPE is an integral part of reducing transmission of COVID-19. We assessed a 5-week pilot project of utilising health science student volunteers as PPE coaches in the adult and paediatric emergency department (ED) during the pandemic. PPE coaches were provided with training, PPE checklist, area for written observations, and feedback surveys. Overall, correct PPE use improved over time. Coaches felt safe, that training was adequate, and part of the team. Factors that contributed to project effectiveness included institutional support, role clarification, and continuous feedback from staff. Our findings support the utilisation of students in IPC projects.